CUSTOMIZAÇÃO DA PLATAFORMA NOTION PARA AUXÍLIO NA APRENDIZAGEM DE ALUNOS COM TDAH - camargo, jaqueline; Pelentir, Nicole; Wonzoski, Fabiano Oliveira (Seminário de Iniciação Científica e Seminário Integrado de Ensino, Pesquisa e Extensão (SIEPE), 2025)
Introduction: The project is based on the challenges faced by students with ADHD in managing school activities, which can compromise academic performance. Notion, due to its flexibility and customization capabilities, was chosen as a tool to meet these specific needs, with the potential to improve student engagement and performance. Objective: The objective of this project is to customize the Notion platform to create a more efficient and accessible learning environment for students with Attention Deficit Hyperactivity Disorder (ADHD). The initiative seeks to facilitate organization, time management, and task monitoring, making the educational process more structured and motivating. Method: The methodology involves the development and adaptation of Notion templates, focusing on features that support organization and planning, as well as the implementation of automations to facilitate task tracking. The project is ongoing and is currently in the phase of improving automations and making adjustments based on user testing. The expected outcome is to provide students with a practical tool adapted to their needs, contributing to a more efficient, accessible, and motivating study environment. Results: Currently, the focus is on creating automations and implementing gamification elements, such as a points and rewards system to stimulate student engagement. The automations are being designed within Notion's basic plan, exploring the free resources of the platform to ensure accessibility and efficiency. The project is ongoing, with continuous research and testing to validate functionalities and ensure they meet student needs. Conclusion: In conclusion, it is expected that this work will result in a functional, accessible resource tailored to the specific needs of students with ADHD, contributing to a more structured, motivating, and efficient learning process. Keywords: Notion; ADHD; Organization.